DINAMIKA DAN POLA KEMISKINAN DI KABUPATEN LOMBOK TIMUR - KABUL, LALU MUH. (Universitas Mahasaraswati Mataram, 2020)
This study discusses poverty dynamicsand its pattern wherethe significance of the study is to accelerate implementation of poverty alleviation effectively. The study method used is mixed method, quantitative and qualitative. The result of study in 2016-2018 indicatedthat number of people who moved out poverty (mover) larger than who move into poverty (faller).Meanwhile, povery pattern indicated that number of people who experienced transient poverty (50.12 percent) larger than number of people who experienced chronical poverty (48.63 percent). The implication of the study is not only number of people changed each year, but also their poverty status. Therefore, up dating of povery data must be carried out regularly each year